ABC transporters at the blood-brain barrier - Mahringer, Anne; Fricker, Gert (Expert opinion on drug metabolism & toxicology, 2016)
Introduction: The blood-brain barrier (BBB) possesses an outstanding ability to protect the brain against xenobiotics and potentially poisonous metabolites. Owing to this, ATP binding cassette (ABC) export proteins have garnered significant interest in the research community. These transport proteins are predominantly localized to the luminal membrane of brain microvessels, where they recognize a wide range of different substrates and transport them back into the blood circulation.Areas covered: This review summarizes recent findings on these transport proteins, including their expression in the endothelial cell membrane and their substrate recognition. Signaling cascades underlying the expression and function of these proteins will be discussed as well as their role in diseases such as Alzheimer’s disease, epilepsy, amyotrophic lateral sclerosis and brain tumors.Expert opinion: ABC transporters represent an integral part of the human transportome and are of particular interest at the blood-brain barrier they as they significantly contribute to brain homeostasis. In addition, they appear to be involved in myriad CNS diseases. Therefore studying their mechanisms of action as well as their signaling cascades and responses to internal and external stimuli will help us understand the pathogenesis of these diseases.
Gesehen am 25.05.2020